Development and Evaluation of a Human Skin Equivalent in a Semiautomatic Microfluidic Diffusion Chamber - Júlia Tárnoki-Zách; Elod Mehes; Zsófia Varga-Medveczky; Dona Greta Isai; Nandor Barany; Edina Bugyik; Zsolt Revesz; Sándor Paku; Franciska Erdo; Andras Czirok (MDPI AG, 2021)
There is an increasing demand for transdermal transport measurements to optimize topical drug formulations and to achieve proper penetration profile of cosmetic ingredients. Reflecting ethical concerns the use of both human and animal tissues is becoming more restricted. Therefore, the focus of dermal research is shifting towards in vitro assays. In the current proof-of-concept study a three-layer skin equivalent using human HaCaT keratinocytes, an electrospun polycaprolactone mesh and a collagen-I gel was compared to human excised skin samples. We measured the permeability of the samples for 2% caffeine cream using a miniaturized dynamic diffusion cell ("skin-on-a-chip" microfluidic device). Caffeine delivery exhibits similar transport kinetics through the artificial skin and the human tissue: after a rapid rise, a long-lasting high concentration steady state develops. This is markedly distinct from the kinetics measured when using cell-free constructs, where a shorter release was observable. These results imply that both the established skin equivalent and the microfluidic diffusion chamber can serve as a suitable base for further development of more complex tissue substitutes.